Trauma Severity and Its Impact on Local Inflammation in Extremity Injury—Insights From a Combined Trauma Model in Pigs - Horst, Klemens; Greven, Johannes; Lüken, Hannah; Zhi, Qiao; Pfeifer, Roman; Simon, Tim P.; Relja, Borna; Marzi, Ingo; Pape, Hans-Christoph; Hildebrand, Frank (Frontiers in Immunology, 2020)
Background: Extremity fracture is frequently seen in multiple traumatised patients. Local posttraumatic inflammatory reactions as well as local and systemic interactions have been described in previous studies. However, trauma severity and its impact on the local immunologic reaction remains unclear. Therefore, fracture-associated local inflammation was investigated in a porcine model of isolated and combined trauma to gain information about the early inflammatory stages. Material & Methods: Polytrauma (PT) consisted of lung contusion, liver laceration, femur fracture, and controlled haemorrhage. Monotrauma (MT) consisted of femur fracture only. The fracture was operatively stabilised and animals were monitored under ICU-standard for 72 h. Blood, fracture hematoma (FH) as well as muscle samples were collected throughout the experimental period. Levels of local and systemic pro- and anti-inflammatory as well as angiogenetic cytokines were measured by ELISA. Results: Both groups showed a significant decrease in pro-inflammatory IL-6 in FH over time. However, concentrations in MT were significantly higher than in PT. The IL-8 concentrations initially decreased in FH, but recovered by the end of the observation period. These dynamics were only statistically significant in MT. Furthermore, concentrations measured in muscle tissue showed inverse kinetics compared to those in FH. The IL-10 did not present statistical resilient dynamics over time, although a slight increase in FH was seen by the end of the observation time in the MT group. Conclusions: Time-dependent dynamics of the local inflammatory response were observed. Trauma severity showed a significant impact, with lower values in pro- as well as angiogenetic mediators. Fracture repair could be altered by these trauma-related changes of the local